#TITLE_ALTERNATIVE# - HUTAHAEAN (NIM 23198028), RAMSES
Dynamic analysis of a large rotor bearing system usually has too many degrees of freedom, a direct dynamic analysis by means of the finite element analysis method, in general is not practicable. The objecrive the substructure method is to reduce the time and thus the cost of predictive calculations for the behavior of large structure, another advantage if mathematical model of one or more components of the structure are unknown, we can identify the structrure component using identification technique, and assembly the identified components to main substructure. The results of the substructure analysis using identification data are compared with finite element analysis.